Minutes of the Twelfth Regular Meeting of the Rocky Mountain Coal Mining Institute, Held at Denver, Colorado, February 25 and 26, 1921 - February 25th. Morning Session (Rocky Mountain Coal Mining Institute, 1921)
The meeting was called to order by the President, Mr. B. J. Matteson, in Dining Room No. I of the Albany Hotel, at 10 a. in., with thirty members present. After an address of welcome by the President, the Convention proceeded to business. First on the program was the reading of the minutes of the' previous meeting, by" the Secretary.' There being no alterations or amendments they were approved as read. A motion was regularly moved and carried that the Secretary provide membership cards to be mailed, or presented, to the members upon payment of dues in lieu of the receipt which has heretofore been used since the organization of the Institute. Mr. R. A. McAllister then presented his paper, the subject, being: "Mine Haulage." Mr. Robert A. Marshall had prepared a paper upon the subject of "Efficiency in Shot Firing," but as he was unavoidably absent, it was read by Mr. Sam Andrews. At the conclusion of the reading of Mr. Marshall's paper, Mr. Andrews presented his own *paper: "Some Facts About Coal Mining." As Mr. George A. Brown was unable to be present, the President requested Mr. R. S. Morton to read his paper, subject: "Flexoid Tubing and Its Application to Coal Mines as a Means of Temporary Ventilation." There being no further business 'the meeting adjourned.